Generation of rogue waves with predefined steepness - Clauss, Günther F.; Schmittner, Christian E; Klein, Marco (Volume 2: Ocean Engineering and Polar and Arctic Sciences and Technology, 2006)
For the deterministic investigation of cause-reaction relationships and for analyzing structure responses due to special wave scenarios methods for the precise generation of tailored wave sequences are required. In this paper we present an optimization approach for the experimental generation of wave sequences with defined characteristics, in particular with predefined wave steepness. Firstly, target parameters, such as wave crest front steepness, wave height and wave period at a particular time are defined for a wave group. Starting with a random phase distribution in frequency domain the phases are optimized in order to satisfy the target parameter in time domain. From this optimized target wave sequence a control signal based on linear wave theory for the wave generator is derived and the wave sequence is registered in a physical wave tank. As nonlinear effects like wave-wave interaction and wave breaking are insufficiently covered by the generation process the registered wave train may differ from the target parameters defined. To improve the accuracy of the measured wave sequence at target location the control signal is iteratively improved by a fully automated optimization process, controlling the wave generator, measuring and analyzing the created waves and modifying the control signal. As a result of the optimization process, a control signal for a wave train, satisfying all target parameters is obtained. The method is applied to generate a breaking rogue wave with defined wave crest front steepness superimposed to irregular seas.